The Rapid Detection of Pork Gelatin in Hard Shell Capsule on Supplement Products Using FTIR and PCA - Badrul, Ahlam Inayatullah; Munir, M Abdurrahman; Riani, I Gusti; Sa’adah, R (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
This study aimed to develop a fast and low-cost detection method to determine the difference between hard shell capsule on supplement products containing pork or non-pork gelatin by using Fourier Transform Infrared (FTIR) spectroscopy and Partial Component Analysis (PCA). Twelve samples of hardshell capsules were used, among which Eight samples were pure made from pork and some of them adulterated with cow. The samples were detected before using real-time PCR to determine the identity of the samples. All the gelatin samples were measured with the FTIR spectrophotometer in the re?ection mode. Spectra were collected in the wavenumber range from 4000-650 cm-1. The results show that the PCA model with the data were pre-processed before PCA was performed. The absorbance data from FTIR were pre-processed using Savitsky-Golay smoothing technique and continued with normalization by peak normalize before subjected to PCA. This newly developed method is fast, involves simple sample preparation and is low cost.